Positive Psychology-Based Psychoeducation to Improve Generation Z Self-Esteem - Alda Syafira; Djudiyah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aimed to examine the effectiveness of a positive psychology-based digital psychoeducation intervention in improving self-esteem among Generation Z individuals who experience upward social comparison on social media. A quasi-experimental one-group pretest-posttest design was employed, involving 13 participants selected through purposive sampling. The intervention was delivered digitally over four days and included gratitude journaling and character strengths components. Self-esteem was measured using the Rosenberg Self-Esteem Scale before and after the intervention. Results showed that the mean self-esteem score increased from 26.69 at pretest to 28.31 at posttest, with a medium effect size (Cohen's d = 0.50). However, the paired sample t-test indicated that this increase was not statistically significant (t = -1.819, df = 12, p = 0.094). These findings suggest a promising, though inconclusive, direction of change, indicating that brief digital positive psychology interventions may hold potential benefits for improving self-esteem that warrant further testing with larger samples and a control group